2015
DOI: 10.3928/02793695-20151021-01
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Depression in Older Home Health Patients

Abstract: Depression is common in older home health patients and increases their risk of adverse outcomes. Depression screening is required by Medicare’s OASIS. The Depression CAREPATH was developed as a feasible strategy for home health nurses to manage depression in their medical patients. The protocol builds on nurses’ existing clinical skills and is designed to fit within routine home visits. Major components include ongoing clinical assessment, care coordination, medication management, education and goal setting. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mental health home visits and treatment have been found to be associated with both positive clinical outcomes and substantially lower costs of care compared with conventional outpatient care, especially among elderly people with depression [ 34 , 35 ]. There is also evidence that mental health home visits that combine community-based and hospital-based home services can improve the stabilisation of clients’ illnesses and enhance their daily living and communication abilities [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mental health home visits and treatment have been found to be associated with both positive clinical outcomes and substantially lower costs of care compared with conventional outpatient care, especially among elderly people with depression [ 34 , 35 ]. There is also evidence that mental health home visits that combine community-based and hospital-based home services can improve the stabilisation of clients’ illnesses and enhance their daily living and communication abilities [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…An interventional study that used a nurse case manager to provide a home visit program that included case management, care planning, health education and lifestyle modification found that loneliness and depressive symptoms decreased in intervention group participants when compared to those in the control group (Taube, Kristensson, Midlov, & Jakobsson, 2018). Another study, which adopted an individual-centred approach and combined ongoing clinical assessment, medication management, care coordination, education, and goal setting, was proven to be successful in improving depressive symptoms in frail older adults with confirmed depressive state, though no effect was observed for community-dwelling older adults without the confirmed depression state (Bruce, 2015). However, little is known about the psychological impact of a nurseled proactive self-care program on independent, non-frail community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%
“… 149 CAREPATH seeks to integrate depression care into routine home health practice; home health nurses are trained to identify and manage depression as part of routine home visits and discharge planning, and coordinate depression care with the patients’ primary care provider and mental health specialist. 150 …”
Section: Opportunities and Recommendations For Promoting Mental Healt...mentioning
confidence: 99%